Global human exposure of atmospheric polybrominated diphenyl ethers: Variation patterns of exposure pathways and phase contributions - Pengtuan Hu; Shimin Zhong; Jin Guo; Mengyao Wang; Shiyu Shi; Donghai Liu; Hao Yu; Fujie Zhu; Yi-Fan Li; Zhiguo Cao (Environment International)
At present, there are still certain limitations in the research on the pathways and phase contributions of semi-volatile organic compounds (SVOCs) to human exposure in the atmosphere. This study clarified the contribution rates of inhalation and dermal exposure of particulate and gaseous polybrominated diphenyl ethers (PBDEs) on a global scale, as well as their influencing factors and mechanisms. Data on gaseous PBDEs were collected from 125 cities across 38 countries and regions to predict size-resolved particulate exposure levels, utilizing our previous method for inhalation alongside a size-dependent prediction method for dermal exposure developed in this study. The global distribution of PBDEs in gas phase showed a significant negative correlation (r = − 0.40, p < 0.05) with the level of per capita GDP, resulting in a similar pattern of human exposure to atmospheric PBDEs. The highest daily intake was found in Africa (75.4 pg/(kg·day)), followed by Asia (21.8 pg/(kg·day)), North America (5.38 pg/(kg·day)) and Europe (1.92 pg/(kg·day)). Inhalation pathways dominated human exposure to atmospheric PBDEs. The contributions of particle phase to the total human exposure presented a pattern of Europe (26.8 %) < North America (33.5 %) < Asia (43.7 %) < Africa (59.8 %), exhibiting a significant positive correlation with TSP (r = 0.79, p < 0.01). An important finding was that the fluctuation of TSP around 70 μg/m3 may lead to alterations in the primary exposure phase for humans. Temperature exerted negative effects on the particulate contribution of low-brominated PBDEs varying in different individuals. In this study, a web platform was also developed, which offered predictions of inhalation and dermal exposures to SVOCs, obviously improving the efficiency of evaluating human exposure to atmospheric PBDEs and researching their exposure patterns.